2016
DOI: 10.1371/journal.pone.0151230
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feeling, Negative Meaning: Visualizing the Mental Representations of In-Group and Out-Group Smiles

Abstract: Even though smiles are seen as universal facial expressions, research shows that there exist various kinds of smiles (i.e., affiliative smiles, dominant smiles). Accordingly, we suggest that there also exist various mental representations of smiles. Which representation is employed in cognition may depend on social factors, such as the smiling person’s group membership: Since in-group members are typically seen as more benevolent than out-group members, in-group smiles should be associated with more benevolent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
1
10
0
2
Order By: Relevance
“…Altogether, our results are concordant with Ratner et al . ()'s suggestion that mere membership in an arbitrary group can prompt divergent mental representations (and expectations) of in‐group and out‐group facial features (see also Paulus et al ., ), and further highlight how such polarized expectations can impact the very first stages of face processing.…”
Section: Discussionmentioning
confidence: 96%
“…Altogether, our results are concordant with Ratner et al . ()'s suggestion that mere membership in an arbitrary group can prompt divergent mental representations (and expectations) of in‐group and out‐group facial features (see also Paulus et al ., ), and further highlight how such polarized expectations can impact the very first stages of face processing.…”
Section: Discussionmentioning
confidence: 96%
“…Generally, the ingroup CI was judged more positively than the outgroup CI by independent raters. This work was extended by Paulus, Rohr, Dotsch and Wentura (2016), who visualised the interpretation of an ingroup vs. outgroup smile after assignment to minimal groups (Paulus et al, 2016). The CIs showed that smiles of ingroup members signal more benevolence than those of outgroup members.…”
Section: Top-down Biasesmentioning
confidence: 92%
“…15,17]. Take for instance the mental representation of other-group faces: studies have shown that individuals represent the facial appearance of someone more positively when they come from the same social group than when they come from another social group [12,37,53]. In other…”
Section: Methodsmentioning
confidence: 99%